Ciência e literatura na Itália do século XX - Mauro, Sergio [UNESP] (My University, 2010)
This essay intends to analise the relationship between science and literature in Italy in the 20th century. I will remark the considerations about science and literature made by italian writers like Calvino and Levi.

O presente ensaio visa à análise das complexas relações entre as ciências e as artes na Itália do século XX. O destaque será dado às considerações sobre o papel da ciência na sociedade do século XX feitas por romancistas e contistas italianos do nível de Calvino e Levi.
Science and literature in Italy in the 20th century
Keywords: Italian narrative of the 20th Century; Science and technology; Relationship between sciences and arts; Narrativa italiana do século XX; Ciência e Tecnologia; Relações entre ciências e artes